The Monitoring of Structural Quality of Silicon-Sapphire Interface by the Surface Photovoltage Method - S. D. Fedotov; S. P. Timoshenkov; E. M. Sokolov; V. N. Statsenko (Известия высших учебных заведений России: Радиоэлектроника)
Heteroepitaxial silicon-on-sapphire (SOS) wafers with a layer thickness of 200 and 600 nm were fabricated by the vapor phase  epitaxy with monosilane as a precursor. The assessment of structural quality of silicon-sapphire interface was carried out by the surface photovoltage method (SPV) and X-ray reflectometry. Technological parameters of the manufacturing process that affecting to the  amount of SPV signal were determined via SOS quality monitoring.  We conclude that deposition temperature and the growth rate are  most important process parameters in this cause. It was found that  SPV method can be used as monitoring method of SOS fabrication  process, because SPV signals are correlated with Xray reflectometry  results. Probably, SPV method allowed to evaluate the structural and electrophysical parameters of silicon- sapphire interface. SOS device performances as function of SPV signal were determined. The leakage current of test pchannel MOS transistor in the closed state  was on 2-16 nA when SPV signal higher than 450 mV and the  leakage current was approximately 4 nA when SPV signal lower than 450 mV.